(untitled) (Journal of Ideas in Health, 2025)
Background: An ectopic pelvic kidney is a rare congenital anomaly with a high incidence of complications such as reflux, the pelviureteric junction (PUJ) obstruction, nephrolithiasis, and even renal failure. We here report a case of retrograde intrarenal surgery (RIRS) for the treatment of right pelvic kidney stones. Case presentation: A 65-year-old male presented to the urology clinic at Life Hospital, Kalar, Iraq, on September 10, 2024, with complaints of lower abdominal pain, microscopic hematuria, and dysuria. The patient had a medical history of cardiovascular and unhealthy lifestyle-related diseases. Physical examination revealed lower abdominal pain without fever. Serum creatinine was 1.4 mg/dL and HbA1c was 8.7%, with microscopic hematuria and pyuria in urinalysis. Contrast-enhanced CT revealed an ectopic right iliac kidney with moderate hydronephrosis and two renal stones (11 mm and 13 mm). Flexible ureterorenoscopy (fURS) with Holmium: YAG laser stone dusting was performed under spinal anesthesia. The procedure lasted 50 minutes, achieving complete stone clearance. The patient was discharged the same day without complications, and follow-up confirmed successful outcomes. Conclusion: A single-session RIRS has successfully disintegrated the stone. Proper preoperative assessment and selection of the most suitable surgical procedure are critical for successful treatment.